A study on the use of tractors and factors influencing selection of tractors among Kelantan farmers / Mohamed Samsudin Ismail - Ismail, Mohamed Samsudin (1992)
The study is done based on the use of primary and secondary data. The primary data consist of questionaires and observations. Two hundred sets of questionaires were distributed to respondents in the ten districts in Kelantan. About eighty sets of questionaires were collected and these samples were taken to represent the whole findings of the study. The observations were made by the writer on the situation where the demand of tractors and the actual sales transaction by the sales agents or dealers and the situations where tractors were being operated in the plantations, estates or farms. The secondary data was collected from various agricultural agencies, magazines, hand-outs from tractor dealers, annual reports, seminar papers and many others. This secondary data collected gives much relevant information to support the findings of this study.